Introduction to Small Talk as Indonesian Society's Communication Culture for Chiang Mai University Students - Asteria, Prima Vidya; Saksono, Lutfi; Surana, Surana; Parmin, Jack; Sariah, Sariah; Pramesty, Meydiana Dyah; Pawoko, M. Wisnu (Dimar : Jurnal Pengabdian Masyarakat, 2025)
The purpose of this community service is to provide an introduction to the culture of small talk to BIPA students from Thailand. This community service was carried out in 3 stages with twelve Chiang Mai University Thailand students as partners who were taught by two BIPA lecturers from Surabaya State University and mentored by a lecturer from Chiang Mai University. The material taught was Indonesian communication culture, especially small talk. Learning was carried out during three hybrid meetings, which contained the following details: 1) The first online meeting, which contained the delivery of small talk as a communication culture of Indonesian society and the importance of cross-cultural understanding in a multicultural context, 2) The second online meeting, namely mentoring for making projects, and 3) The third offline meeting, containing presentations of previously given projects, reinforcement of materials, and reflection on activities. The results of the learning process showed that Chiang Mai University students responded positively to the introduction to Indonesian communication culture activities that were held, they verbally expressed their happiness in getting this material and even submitted assignments before the deadline given.